Challenge of Retinoblastoma in Mexico in 2020: Perspectives and Solutions - Lucas A. Garza-Garza; Raúl E. Ruiz-Lozano; Genaro Rebolledo-Méndez; Ismael Ibarra-Nava; Héctor J. Morales-Garza; David Ancona-Lezama (Journal of Ophthalmology)
Early diagnosis and positive outcomes of retinoblastoma in childhood have been positively correlated with the economic wealth of high-income countries (HICs) worldwide. Adequate curability and survival rates, adherence to treatment, presence of poor prognostic initial clinical signs, and metastatic disease at diagnosis appear to have a less favorable picture in low-income countries (LICs). However, this is not always the case. An example is Argentina, where disease-free survival rates of retinoblastoma are notably higher than expected when taking into consideration its economic situation. Unfortunately, as in other Latin American LICs, retinoblastoma outcomes in Mexico are worrisome. Interestingly, the Human Development Index (HDI) in Mexico varies widely between its different geographical regions. While in some states, the HDI resembles those of high-income countries, and in others, the opposite is observed. A unifying picture of Mexico’s developmental status, health resources, indicators, and other factors possibly influencing outcomes in retinoblastoma is currently unavailable. The present review explores the previously mentioned factors in Mexico and compares them to other countries. Additionally, it recommends solutions or enhancements where possible.